“The malaria vaccine should be Dead on Arrival”: Exploring Health Discourse and Misinformation on KingsChat, a Nigerian Pentecostal Social Networking Platform - Whiting, Peter; Partridge, Virginia; Ndulue, Emily Boardman; Olaniran, Samuel; Bermejo, Fernando (AoIR Selected Papers of Internet Research, 2026)
As digital technologies reshape how faith communities communicate and operate, religious leaders extend their influence into online spaces where spiritual and health-related beliefs converge. This study is the first to investigate health discourse and misinformation on KingsChat, the social networking platform of the Christ Embassy megachurch in Nigeria led by Pastor Chris Oyakhilome, a known source of COVID-19 conspiracy theories and health misinformation.By scraping public KingsChat posts matching selected health search terms in addition to any posts from individuals in Christ Embassy church leadership, a dataset of 12,443 posts was collected. Keyword analysis identified various health discourse patterns, particularly around misinformation concerning COVID-19, vaccines, faith healing and malaria. To better understand health-related content in these posts, a random sample of posts containing health terms was manually coded. This found that 35% of health-related posts contained a debunked or unsubstantiated health-related claim. The largest two categories of misinformation involved faith healing and conspiratorial narratives about vaccines. Additional investigation of the external URLs linked to from KingsChat posts also exposes cross-platform interactions in the way the church distributes and amplifies health messages across digital spaces.These findings underscore challenges facing public health officials working with communities where Christ Embassy church is influential. Understanding the interplay of digital media ecosystems, as well as the motivations and strategies for spreading health information online, will help researchers propose effective interventions and public health measures while respecting community norms.